Design And Develop Of A Condo Property Management System With Mobile Application And Web-Based Management Dashboard - Teh, Keh Boon (2020)
It is a tough job to manage condominium and gate communities. The traditional way of managing condo property is unable to handle a lot of issues efficiently. Hence, we should make use of Information and Communication Technology to manage the condo property more smartly and easily. This will be able to help the management communicate with tenant easily, while the tenant can report issues, get latest announcement and pay the bill without going outside. The adopted software development methodology is rapid application development as the integration can be built throughout the process. The project will be involved in developing web application and mobile app for different users. In a nutshell, this project had achieved the objectives by using the solution proposed.